Phonological processing skills in bilingual (Catalan and Spanish) students with and without dyslexia - Riembau, Cati; Ivern, Ignasi; Serrat, Elisabet (Revista de Investigación en Logopedia, 2025)
To examine literacy learning in bilingual contexts, this study assessed phonological processing skills in a sample of bilingual students, both with and without dyslexia. It also aimed to determine whether the stage of literacy acquisition affects phonological skills in bilingual children with and without dyslexia. The participants were 113 Catalan/Spanish bilinguals, aged 8 to 14 years, attending middle and upper primary school, as well as early secondary school. The study assessed accuracy in the following phonological processing skills: phonological awareness (using phonemic awareness tests), phonological recoding (through a pseudo-word reading task), and phonological memory (using a pseudo-word repetition task). Overall, the results showed differences between students with and without dyslexia across all tasks, but no differences were found between the two languages studied. Results by educational stage revealed that differences in the phonemic awareness task diminished with age, while differences in pseudo-word reading persisted. Additionally, differences were observed among middle and secondary school participants without dyslexia, with better accuracy in the phonemic awareness task in Spanish. The results are discussed in relation to previous studies and the transparency and opacity of the languages involved.
Keywords: phonological processing skills; dyslexia; childhood; bilingualism